Pola Pembelajaran Toilet Training Anak Usia Sekolah Bagi Anak Enuresis di SD Negeri Ledug Kabupaten Banyumas - Lutfiannisa Fadhillah; Deisy Sri Hardini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This research aimed to find out the pattern of toilet training learning for school-age children with enuresis in SD Negeri Ledug, Banyumas Regency.Methods: This was qualitative research with a phenomenological approach. Five people were taken as the research samples by combining purposive sampling and snowball sampling techniques. The data were obtained through in-depth interviews.Results: The informants were 33-48 years old, graduated from elementari school, junior high school, vocational school, and worked as housewives. The children were male and female, aged 6-7 years. The toilet training carried out by the informants began by telling the children about how to urinate and defecate properly. This learning was done by asking children to practice directly so that they were accustomed to do it.Conclusion: The themes found in the research were understanding toilet training, the perspective of toilet training for children, time to teach toilet training, perception of the impact if children are given the toilet training late, techniques to teach toilet training, obstacles in toilet training, overcoming consultation problems with health workers, overcoming consultation problems with family, perception of feelings of handling children with enuresis, and causes of enuresis in children. Keywords: Enuresis, Learning Pattern, Toilet Training, School Age